Theories of education and educational research: Contributions to the continuous education of teachers (Research, Society and Development, 2024)
Scientific research in the educational field can become a great ally with regard to the construction of new knowledge and critical training for education professionals. It is through research that we will seek to become aware that we are producers of transforming knowledge, facilitating improvement and encouraging pedagogical work. Based on the above, this article aims to address the theories of education in some of its phases and its influence on the preparation of the educator, reflecting on the formation of teachers from the educational research which seeks to follow the course, maintaining a relationship dialectic between theory and practice, that is, from “understanding” to pedagogical “doing”. For the construction of the theoretical foundation of this research, we selected some authors, among them: Batista, Saviani, Suchodolski, Freire and Schnetzler. Discussions point out that teaching as a transforming action in society is renewed from teacher training, which is the result of research based on theories of education.